2018
DOI: 10.4088/jcp.17m11695
|View full text |Cite
|
Sign up to set email alerts
|

Association of Up-Regulated Plasma Adiponectin With Risk of Incident Depression in a Community-Dwelling Elderly Population

Abstract: Up-regulation of plasma adiponectin may precede the onset of clinically significant depression in the elderly, and thus plasma adiponectin level is a potential candidate marker for the risk of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A meta-analysis of 33 studies found significant lower adiponectin levels in patients with MDD compared to healthy controls, with a small effect size (Cao et al, 2018), and some studies found an inverse association between adiponectin levels and depression severity (Formolo et al, 2019). On the other hand, other studies reported an opposite relationship, associating higher adiponectin levels with current depression and with the prospective risk of developing it (Huang et al, 2019;Oh et al, 2018;Yildiz et al, 2017).…”
mentioning
confidence: 99%
“…A meta-analysis of 33 studies found significant lower adiponectin levels in patients with MDD compared to healthy controls, with a small effect size (Cao et al, 2018), and some studies found an inverse association between adiponectin levels and depression severity (Formolo et al, 2019). On the other hand, other studies reported an opposite relationship, associating higher adiponectin levels with current depression and with the prospective risk of developing it (Huang et al, 2019;Oh et al, 2018;Yildiz et al, 2017).…”
mentioning
confidence: 99%